Sex hormone levels in females of different ages suffering from depression - Rong Lei; Yan Sun; Jiawen Liao; Yuan Yuan; Linlin Sun; Yugeng Liu; Xinyu Yang; Wenyou Ma; Zhenjian Yu (BMC, 2021)
Abstract Background There are only a few studies on sex hormones in females of different ages suffering from depression, and their conclusions are not uniform until now. This study aimed to investigate the correlation between the severity of depression in females and factors such as sex hormones and differences in sex hormone levels in females of different ages, exploring variations after treatment. Methods A total of 169 females with depression were selected and divided into the first-episode (91 cases) and recurrent (78 cases) groups. Then, on the basis of their age, the first-episode patients were divided into the young (48 cases, age < 45 years), perimenopausal (20 cases, 45-55 years), and elderly groups (23 cases, age > 55 years); the patients with recurrent depression were classified into the young (37 cases, age < 45 years), perimenopausal (19 cases, 45-55 years), and elderly groups (22 cases, age > 55 years). The patients were assessed in accordance with the International Classification of Diseases of mental and behavioral disorders. The serum progesterone, prolactin, estradiol, and testosterone levels in the patients were measured, and differences in sex hormone levels of the groups were analyzed. Results The estradiol level was negatively correlated with age and the prolactin level was positively correlated with occupation. The severity of depression in females was found to be negatively correlated with age. The serum progesterone and estradiol levels in the young group were significantly higher than those in the elderly group, regardless of the first episode or recurrence. Estradiol levels in the perimenopausal and elderly groups with first-episode depression were significantly higher than those in the same group with recurrent depression. However, there was no significant difference in the serum progesterone, prolactin, estradiol, and testosterone levels in the recurrent group before and after treatment. Conclusions Sex hormone levels, especially estradiol, varied among females of different ages suffering from depression. Recurrent depression also has a certain effect on sex hormone levels in females. Not only should the age and relapse be considered when studying the sex hormone levels of females with depression, but also attention should be paid to whether the patients have used antidepressants before their sexual hormonal testing.